Hubungan Status Gizi Dengan Kejadian Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Pedan Klaten - Ariana, Siwi, Bejo Raharjo, SKM, M.Kes, Kusuma Estu Werdani, SKM., M.Kes (2015)
Pneumonia is the main cause of toddlers death in the world. Pneumonia causes more than 2 million toddlers died each year. Pneumonia is caused by lung inflamation which is make the breathing becomes sick and oxygen intake becomes slightly. The objectives of the research was to know the ratio between nutritional status and the incident of pneumonia on toddlers in Puskesmas Pedan Klaten area. The type of the research was observational analysis with case control study design. The case population in this research was 67 toddlers suffering from pneumonia on March - May 2015, whereas the control population toddlers who ware not suffering from pneumonia and live near the case respondent. The sample selection on case group were 40 toddlers and the control group were 40 toddlers which were selected by using Sample Random Sampling. While the statistical test technique used Chi Square test. Based on the findings in the case group obtained under five suffering from pneumonia with less nutritional status for 24 people (60%) and in the control group who experienced malnutrition status for 14 (35%). The result of the research explains that there was a relation between nutritional status and the incident of pneumonia on toddlers in Puskesmas Pedan Klaten area (p = 0.025; OR = 2.786; 95% CI = 1.125 to 6.899). The suggestions for the measurement weight/high toddler when Posyandu, knowledge and to implement it on society about nutrition to prevent the incident of pneumonia on toddlers. Keyword: pneumonia, nutritional status, toddlers.